A general method for the synthesis of 5-difluoromethyl isoxazoles. Issue 52 (24th December 2020) - Lin, Jiawei; Wu, Wei; Weng, Zhiqiang
Graphical abstract: Highlights: A method for synthesis of 5-(chloro)difluoromethyl isoxazoles was developed. Various 5-(chloro)difluoromethyl isoxazoles were isolated in moderate to excellent yields. A variety of functional groups were tolerated. Abstract: An efficient reaction of vinyl azides with difluoroacetic anhydride or chlorodifluoroacetic anhydride has been developed. It involved sequential difluoroacetylation of vinyl azides, followed by deprotonation, cyclization, and dinitrogen elimination, providing a convenient synthesis of both 5-difluoromethyl and 5-chlorodifluoromethyl isoxazoles at yields up to 89%.